Castle Rock, the complete series [videorecording (Blu-Ray)] - Shaw, Sam; Thomason, Dustin (Warner Bros. Entertainment, 2021)
Characters and themes from Stephen King's multiple universes converge in the fictional town of Castle Rock. In season two a feud between warring clans comes to a boil when budding psychopath Annie Wilkes, nurse from hell, gets waylaid in Castle Rock. And as the town celebrates its 400th anniversary, Castle Rock's first settlers -- including Henry Deaver -- find themselves joining in the festivities.